[Rezension von: Oakes, Peter, Empire, economics, and the New Testament] - Coleman, Rachel L. (The journal of theological studies, 2021)
Empire, Economics, and the New Testament is a collection of ten essays representing more than two decades of Peter Oakes’s research into the world inhabited by the New Testament writers and their audiences. His particular investigative interest has been the use of archaeological evidence and socioeconomic models to illuminate the ways in which first-century audiences would have read or heard the New Testament writings. Oakes’s preface lays out the chronological development of his research and the background of chapters 2-10 (all previously published essays). Within Empire, however, the essays are helpfully grouped around three major topics (house church, economics, empire).